Combat trauma-associated invasive fungal wound infections: epidemiology and clinical classification. (18th March 2014) - WEINTROB, A. C.; WEISBROD, A. B.; DUNNE, J. R.; RODRIGUEZ, C. J.; MALONE, D.; LLOYD, B. A.; WARKENTIEN, T. E.; WELLS, J.; MURRAY, C. K.; BRADLEY, W.; SHAIKH, F.; SHAH, J.; et al.
SUMMARY: The emergence of invasive fungal wound infections (IFIs) in combat casualties led to development of a combat trauma-specific IFI case definition and classification. Prospective data were collected from 1133 US military personnel injured in Afghanistan (June 2009–August 2011). The IFI rates ranged from 0·2% to 11·7% among ward and intensive care unit admissions, respectively (6·8% overall). Seventy-seven IFI cases were classified as proven/probable ( n  = 54) and possible/unclassifiable ( n  = 23) and compared in a case-case analysis. There was no difference in clinical characteristics between the proven/probable and possible/unclassifiable cases. Possible IFI cases had shorter time to diagnosis ( P  = 0·02) and initiation of antifungal therapy ( P  = 0·05) and fewer operative visits ( P  = 0·002) compared to proven/probable cases, but clinical outcomes were similar between the groups. Although the trauma-related IFI classification scheme did not provide prognostic information, it is an effective tool for clinical and epidemiological surveillance and research.